Feasibility of N1-P2 Habituation to Differentiate Loudness Levels - Mohamed Aminuddin, Mai Mariam; Mustaffa, Izadora; Saipullah, Khairul Muzzammil (2012)
In the present study, the feasibility of habituation correlates of N1-P2 component of late auditory evoked potential to differentiate loudness levels was investigated. In ten normal hearing subjects, it was shown that habituation correlates of N1- P2 is able to differentiate between acceptable loudness levels (comfortable loudness and comfortable but loud) and strong and high loudness levels (loud, upper level and uncomfortable loudness level (UCL)). Therefore, the proposed approach is promising for the development of objective setting method for hearing devices, especially to estimate the level of UCL.